Genealogy of Economical Halal from Before and After be Appointed The Regulation of Halal Product - Afifatul Munawiroh Wahid; Mahmudah Mahmudah (Rechtenstudent, 2022)
This research is study based on library reseacrh. The grand theme of this research is Genealogy of Economical Halal  from Before and After be appointed the Regulation of Halal Product. Three important questions in this research. Firstly,what is genealogy of economical halal? Secondly,  how was the genealogy of economical halal before be appointed the regulation of halal product? Thirdly, how was the genealogy of economical halal after be appointed the regulation of halal product? With a content analysis approach to explain the meaning of halal genealogy economy. Meanwhile, to explain how how was the genealogy of economical halal before be appointed the regulation of halal product was explained by a historical approach. The result of research is the halal genealoggy in Indonesia has existed since Islam entered with traders through trade routes in the archipelago. This happened when Indonesia was also colonized by the Portuguese.  In essence, the halal aspect of the economy from the colonial period to the reformation period didn’t change in terms of its essence. However, the concept of halal economy has changed in the aspect of trend which is able to  aadapt to the pattern of development of the times.